2007
DOI: 10.1080/02841850701663442
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphological changes after renal X-ray arteriography using iodine and gadolinium contrast media in an ischemic porcine model

Abstract: In ischemic porcine kidneys, the histomorphological changes caused by Gd-CM are similar to those caused by I-CM. Vacuolation appears to be independent of the osmolality and viscosity of the CM, and does not seem to be an indicator of renal impairment. "High-osmolal" Gd-CM are more nephrotoxic than "low- and iso-osmolal" I-CM when compared in equal volumes of concentrations, resulting in equal X-ray attenuation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 46 publications
(81 reference statements)
1
8
0
Order By: Relevance
“…In addition, The impact of iodixanol also persisted longer than the other agent. The result is similar to the detection of Elmstahl et al ( 2007 ). The detection might also indicate that the increased quality enhancement observed with iodixanol injection might provide improved images diagnosis and detailed descriptions of several organic disease.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, The impact of iodixanol also persisted longer than the other agent. The result is similar to the detection of Elmstahl et al ( 2007 ). The detection might also indicate that the increased quality enhancement observed with iodixanol injection might provide improved images diagnosis and detailed descriptions of several organic disease.…”
Section: Discussionsupporting
confidence: 90%
“…It is unclear how much of a contribution to hyperintensity is due to gadolinium retained in the vasculature and how much is due to gadolinium that has entered the brain parenchyma. Gadolinium has been detected in the skin (a tissue known to retain high gadolinium for all GBCAs) of rats up to 364 days post dosing 25 . Our data show an initial rapid clearance up to 4 weeks, which diminishes thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…In an experimental study, at the high dose of gadoversetamide ( (11). Furthermore, the same authors have also demonstrated that ICA (Iohexol) molecules were less nephrotoxic than the gadolinium chelates (gadopentetate and gadodiamid) in ischemic porcine kidneys (12).…”
Section: Discussionmentioning
confidence: 93%